Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Corporate Governance Terhadap Corporate Social Responsibility - Adelheit Advelia Sijum; Any Rustia Dewi (University of Merdeka Malang, 2021)
The purpose of this study was to test the influence of profitability, liquidity, company size, and corporate governance on the disclosure of corporate social responsibility (CSR) in food and beverage companies listed on the Indonesia Stock Exchange for the period 2017-2019. This research is a research design using quantitative approach. The type of research data used is secondary data, while the data source is obtained through the www.idx.co.id. The population in this study is food and beverage companies listed in idx period 2017-2019. Samples used in this study were selected using purposive sampling method and obtained as many as 36 samples. The data analysis technique used in this study was multiple linear regression. Independent variables in this study are profitability, liquidity, company size, and corporate governance, while dependent variables are corporate social responsibility (CSR). The results of the analysis showed that variable profitability has no effect on CSR disclosure, while liquidity, company size, and corporate governance have a significant positive effect on CSR disclosure.